Undocumented Immigrant Threat and Support for Social Controls. (4th November 2014) - Chiricos, Ted; Stupi, Elizabeth K.; Stults, Brian J.; Gertz, Marc
Abstract : Popular support for enhanced border and internal controls to deal with undocumented immigration is examined in relation to contextual measures of group threat as well as perceived levels of cultural and economic threat posed by undocumented immigrants. Results from a national survey of non-Latino respondents (N = 1, 364) indicate that presumed threatening context measured in static terms is inconsequential. But when context is measured in dynamic terms that also reflect dispersion and potential contact, it significantly predicts support for border controls. Perceived threats are stronger predictors of support for enhanced controls than either contextual indicators of presumed threat or individual characteristics of respondents. Results also show that perceived economic and cultural threats mediate the effects of individual respondent characteristics and dynamic contextual conditions as well. Implications for future research on immigrant threat emphasize the importance of context measured in both change and dispersion-related terms and responses to threat that distinguish alternative dimensions of control. Future work should also consider that perceptions of threat may not only have direct influence on immigration policy preferences but can mediate the effects of context and individual characteristics on those preferences.